A Tribute to Dr. Willy Lens. Issue 3 (13th July 2016) - Vansteenkiste, Maarten; Fernandez, Lennia; Mouratidis, Athanasios
Dr. Willy Lens, born on December 10 th, 1943, passed away on August 29 th, 2014. With his passing, the motivation community has lost a seminal member, a mentor, and a friend. Dr. Lens – a Fellow of the Association for Psychological Science and Founding Fellow of the American Educational Research Association – made fundamental contributions to the study of motivation both through his own work and through his caring and thoughtful mentorship of a large community of scholars. With this tribute, we want to honor Dr. Willy Lens' significance to psychology and education as well as his positive influence, both personally and professionally, on the lives of dozens of scholars. With his contagious enthusiasm and caring mentorship, Willy was an example for our academic community and with this tribute we express our gratitude for the privilege to have collaborated with him.